2018
DOI: 10.1002/lary.27246
|View full text |Cite
|
Sign up to set email alerts
|

Totally implantable active middle ear implant: Hearing and safety results in a large series

Abstract: 4. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…49,54 The largest review of patients fit with Esteem also confirmed surgical safety with minimal reported adverse events as well complete resolution of tinnitus for many patients after implantation. 49 A few attempts have been made to complete metanalyses of implantable hearing aid performance compared with both conventional hearing aid and unaided performance. Most independent investigations could not be directly compared because of a lack of standardization in performance outcome measures.…”
Section: Outcomes Studies and Limitationsmentioning
confidence: 80%
See 4 more Smart Citations
“…49,54 The largest review of patients fit with Esteem also confirmed surgical safety with minimal reported adverse events as well complete resolution of tinnitus for many patients after implantation. 49 A few attempts have been made to complete metanalyses of implantable hearing aid performance compared with both conventional hearing aid and unaided performance. Most independent investigations could not be directly compared because of a lack of standardization in performance outcome measures.…”
Section: Outcomes Studies and Limitationsmentioning
confidence: 80%
“…The implanted sound processor receives the signal from the sensing lead and filters and amplifies the acoustic signal. [48][49][50][51][52][53][54] The unique feature of this device is the utilization of the tympanic membrane as the "microphone" of the system, allowing the device to be completely implantable. 55 Unfortunately, this utilization of the intact middle ear system as a microphone pick up source necessitates a healthy eardrum and ossicular chain, limiting indications to patients with normal middle ear anatomy 53 (see Table 2).…”
Section: The Med-el Vibrant Soundbridgementioning
confidence: 99%
See 3 more Smart Citations